Opportunity Recognition and Green Entrepreneurial Intention: The Moderating Effect of Entrepreneurship Education - Dita Maharani Suwardi; Amir Machmud; Endang Supardi; Iswanti Iswanti (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2021)
Increasing the entrepreneurial intentions of university students a being crucial issue. The purpose of this study was to determine the effect and analyze the moderator of entrepreneurship education on the relationship between opportunity recognition and green entrepreneurial intentions. This research applied an explanatory survey and questionnaires distributed to 195 students of Economic Education Siliwangi University in Tasikmalaya.  The collected data were analyzed using structural equation modeling (SEM). The results in this study show that opportunity recognition positively impacts students’ green entrepreneurial intention. This study also indicates the role of entrepreneurship education in moderating the relationship between opportunity recognition and green entrepreneurial intention. The implication of the research is to support the formulation of entrepreneurial education initiative that can promote students in entrepreneurial projects either in the present or in the future.Keywords: Entrepreneurship Education, Green Entrepreneurial Intention, Opportunity Recognition.